2012
DOI: 10.3389/fnhum.2012.00062
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing memory performance with rTMS in healthy subjects and individuals with Mild Cognitive Impairment: the role of the right dorsolateral prefrontal cortex

Abstract: A debated question in the literature is the degree of anatomical and functional lateralization of the executive control processes sub-served by the dorsolateral prefrontal cortex (DLPFC) during recognition memory retrieval. We investigated if transient inhibition and excitation of the left and right DLPFC at retrieval by means of repetitive transcranial magnetic stimulation (rTMS) modulate recognition memory performance in 100 healthy controls (HCs) and in eight patients with Mild Cognitive Impairment (MCI). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 51 publications
6
104
0
Order By: Relevance
“…Coppi et al () and Ash et al () reported using the fronto‐parietal–temporal lobes and prefrontal areas, respectively, without specifying the exact target site. Regarding the targeting method, six studies used magnetic resonance imaging‐guided navigation (Cotelli et al , ; Cotelli et al , ; Turriziani et al , ; Rabey et al , ; Anderkova et al , ; Lee et al , ) and three studies used a non‐imaging‐based technique (Ahmed et al , ; Drumond Marra et al , ; Rutherford et al , ), either a 5‐cm rule to locate the DLPFC (Pascual‐Leone et al , ) or an electroencephalography 10–20 system to locate the brain area.…”
Section: Resultsmentioning
confidence: 99%
“…Coppi et al () and Ash et al () reported using the fronto‐parietal–temporal lobes and prefrontal areas, respectively, without specifying the exact target site. Regarding the targeting method, six studies used magnetic resonance imaging‐guided navigation (Cotelli et al , ; Cotelli et al , ; Turriziani et al , ; Rabey et al , ; Anderkova et al , ; Lee et al , ) and three studies used a non‐imaging‐based technique (Ahmed et al , ; Drumond Marra et al , ; Rutherford et al , ), either a 5‐cm rule to locate the DLPFC (Pascual‐Leone et al , ) or an electroencephalography 10–20 system to locate the brain area.…”
Section: Resultsmentioning
confidence: 99%
“…Second, to determine whether the rTMS effect was topographically specific, we applied rTMS over the vertex after memory reactivation (Vertex-R, control site) [6]. We chose the frequency of rTMS on the basis of a recent study showing that 1 Hz rTMS of right lateral PFC enhanced episodic memory performance when delivered during the interval (10 min) between encoding and retrieval [18]. Memory recall was tested on Day 3 (24h post-reactivation) (see Figure 1 and Supplemental Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, this principle is mainly derived from basic studies of motor cortex and does not necessarily apply to other cortical regions and more complex cognitive functions (Sandrini et al, 2011). For instance, Turriziani et al (2012) showed that 1 Hz rTMS (considered to have an inhibitory effect) of right DLPFC enhanced episodic memory while intermittent Theta Burst Stimulation (considered to have a facilitatory effect) of the same region deteriorated memory performance. In addition, there is evidence that 1 Hz rTMS may improve performance of a cognitive task by strengthening the connectivity between taskrelevant brain regions depending on the functional state of the cortex at the time of stimulation (Ward et al, 2010).…”
Section: Discussionmentioning
confidence: 99%